2019
DOI: 10.3390/su11195395
|View full text |Cite
|
Sign up to set email alerts
|

Objective Measurement of the Mode of Commuting to School Using GPS: A Pilot Study

Abstract: Background and objectives: Active commuting to school (ACS) is a promising strategy to increase the daily physical activity (PA) in youths. However, more studies are required to objectively quantify the mode of commuting to school, as well as the health impact of this behavior. Thus, the aims of this study were: (1) to objectively determine the mode of commuting to school using GPS; (2) to quantify the sedentary time, PA levels, energy expenditure, and the steps derived from each mode of commuting; and (3) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Finally, larger buffers size was not used and adolescents' ACS time was not determined. Future proposals should include more objective measurements of this behavior 41 . The strengths of the present study include a large sample of Brazilian adolescents and the use of environmental variables measured objectively and subjectively to understand how much this reflects in ACS.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, larger buffers size was not used and adolescents' ACS time was not determined. Future proposals should include more objective measurements of this behavior 41 . The strengths of the present study include a large sample of Brazilian adolescents and the use of environmental variables measured objectively and subjectively to understand how much this reflects in ACS.…”
Section: Discussionmentioning
confidence: 99%
“…A previous systematic review with meta-analysis, conducted more than 4 years ago, showed that the contribution of walking to school to objectively MVPA on school days ranges from 13 min/day to 17 min/day in secondary-school students and primary-school student, respectively [ 5 ]. Given the increase of ACS studies among children and adolescents in the last years [ 18 , 19 , 20 , 24 , 25 , 26 , 29 , 30 , 31 , 32 , 33 ] it will be also important to carry out an update of this systematic review including not only walking to/from school but also cycling to/from school. Moreover, since walking is usually a light-intensity activity and provides numerous health benefits [ 1 ] it seems interesting to know the contribution of walking and cycling to/from school to light PA levels.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, several authors such as Pizarro et al [ 24 ] and Villa-Gonzalez et al [ 25 ] assessed the commuting-related PA to/from school through both accelerometer and Global Positioning System (GPS). Several authors have suggested that the combination of data from these two objective measures (i.e., accelerometers and GPS) might allow evaluating cycling to school properly [ 24 , 25 ]. Tarp et al [ 20 ] combined GPS, accelerometers, and heart rate to assess commuting-related PA among adolescent who cycled to school.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…49 A total of 42.9% (n = 6) of the included studies were conducted in children (n = 3525) [36][37][38][39]44,49 and 57.1% (n = 8) in adolescents (n = 3602). [40][41][42][43][45][46][47][48] Regarding trip direction, eight of the included studies only assessed the home-school trip, [36][37][38][39][42][43][44][45] and six of the included studies assessed both trips direction (i.e., home-school and school-home) 40,41,[46][47][48][49] (see Table 1 for more details). The device used to measure PA in all included studies was the accelerometer.…”
Section: Study Characteristicsmentioning
confidence: 99%